Comparing the Efficacy of Cognitive-Behavioral Therapy, Brief Intervention, and Combined Intervention on Reducing Social Alienation in COVID-19 Recovery Patients in Andimeshk - Rahmati, Abbas; Ahmadi, Reza; Mashhadizadeh, Shahram; Ghazanfari, Ahmad (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: This study aimed to compare the effectiveness of cognitive-behavioral therapy, brief intervention, and combined intervention on social alienation among COVID-19 recovery patients in Andimeshk. Research Methods and Materials: The method used in this study was a quasi-experimental pre-test post-test design with a control group. The sample consisted of 80 COVID-19 recovery patients covered by comprehensive health centers in Andimeshk, who were randomly assigned to experimental and control groups (each group containing 20 individuals). The experimental group underwent cognitive-behavioral therapy interventions in eight 90-minute sessions held weekly, while the control group received no intervention. Data were collected using the Melvin Seeman Social Alienation questionnaire, and hypotheses were tested using analysis of covariance. Findings: The results showed a significant difference between the effectiveness of cognitive-behavioral therapy and brief intervention on social alienation among COVID-19 recovery patients in Andimeshk; however, no significant difference was found between the effectiveness of cognitive-behavioral therapy and the combined intervention on social alienation among these patients. Conclusion: Based on the findings, it can be concluded that cognitive-behavioral therapy is effective in reducing social alienation, and there is no difference in effectiveness between cognitive-behavioral therapy and the combined intervention (cognitive-behavioral therapy and brief intervention).